The tower of nero eaudiobook - Riordan, Rick (Trials of Apollo, 2020)
The fifth and final installment of the #1 New York Times bestselling Trials of Apollo series has Lester and Meg returning to where it all began: Camp Half-Blood. At last, the breathtaking, action-packed finale of the #1 bestselling Trials of Apollo series is here! Will the Greek god Apollo, cast down to earth in the pathetic moral form of a teenager named Lester Papadopoulos, finally regain his place on Mount Olympus? Lester's demigod friends at Camp Jupiter just helped him survive attacks from bloodthirsty ghouls, an evil Roman king and his army of the undead, and the lethal emperors Caligula and Commodus. Now the former god and his demigod master Meg must follow a prophecy uncovered by Ella the harpy. Lester's final challenge will be at the Tower of Nero, back in New York. Will Meg have a last showdown with her father? Will this helpless form of Apollo have to face his arch nemesis, Python? Who will be on hand at Camp Half-Blood to assist? These questions and more will be answered in this book that all demigods are eagerly awaiting.